2016
DOI: 10.2323/jgam.2016.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Mycothiol protects <i>Corynebacterium glutamicum</i> against acid stress via maintaining intracellular pH homeostasis, scavenging ROS, and <i>S</i>-mycothiolating MetE

Abstract: Mycothiol (MSH) plays a major role in protect-ing cells against oxidative stress and detoxification from a broad range of exogenous toxic agents. In the present study, we reveal that intracellular MSH contributes significantly to the adaptation to acidic conditions in the model organism Corynebacterium glutamicum. We present evidence that MSH confers C. glutamicum with the ability to adapt to acidic conditions by maintaining pH i homeostasis, scavenging reactive oxygen species (ROS), and protecting methionine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…Regeneration of peroxidase and methionine sulfoxide reductase activities requires both the mycoredoxin (Mrx1) and thioredoxin pathways in vitro 10, 12, 13, 16, 17 . Apart from its redox-regulatory role for antioxidant enzymes, MSH also functions in thiol-protection of the methionine synthase MetE by protein S- mycothiolation under acid stress conditions 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Regeneration of peroxidase and methionine sulfoxide reductase activities requires both the mycoredoxin (Mrx1) and thioredoxin pathways in vitro 10, 12, 13, 16, 17 . Apart from its redox-regulatory role for antioxidant enzymes, MSH also functions in thiol-protection of the methionine synthase MetE by protein S- mycothiolation under acid stress conditions 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress caused MetE inactivation by S-mycothiolation, which resulted in methionine synthesis impairment. Under these conditions, MetE protein levels were increased (Follmann et al, 2009;Liu et al, 2016). In E. coli, it is also reported that oxidative stress causes MetE inactivation by S-glutathionylation, which results in methionine limitation (Hondorp and Matthews, 2004).…”
Section: Fig 3 the Effect Of The Growth Phase On Mete Overproductiomentioning
confidence: 87%
“…In vivo ROS levels were measured using the fluorogenic probe 2Âą,7Âądichlorofluorescein diacetate (DCFH-DA) (Sigma-Aldrich, St. Louis, MI, USA) as described by Liu et al (2016).…”
Section: Measurement Of Intracellular Ros Levelsmentioning
confidence: 99%